Influenza: temporal trends in mortality, hospitalization, and vaccination in the older adults population aged 60 and more years, Brazil, 2000–2023 - Moura, Erly Catarina; Cortez-Escalante, Juan Jose; Vieira Cavalcante, Fabrício; Santos, Leonor Maria Pacheco; Dos Santos, Wallace Enrico Boaventura Gonçalves (Frontiers in Public Health, 2025)
ObjectiveTo evaluate the temporal evolution of mortality rates, hospitalization, and vaccination coverage for influenza among the population ≥ 60 years of age in Brazil from 2000 to 2023. Methods A descriptive study with secondary and anonymous data from the Ministry of Health was collected year by year to calculate the rates. Data on the composition of the vaccines were also obtained.ResultsThe data pointed to: (1) an increase in deaths from influenza, especially during the COVID-19 pandemic, but a decrease in 2023 with the registration of 2.5 deaths per 100 thousand inhabitants; (2) reduction in hospitalizations for influenza, but increase during the Covid-19 pandemic and decrease in 2023, with a record of 22 hospitalizations per 100 thousand inhabitants; (3) linear growth in vaccination coverage, reaching 99.4% in 2019, exceeding 100% in 2020 and a sharp drop in subsequent years, reaching the lowest value in the series (63.3%) in 2023; and (4) formulation of vaccines containing three different strains in all campaigns.ConclusionThe impact of Covid-19 on mortality and hospitalization rates from 2020 beyond is evident. The role of the federal government in controlling pandemics and the importance of vaccination, among other measures, are highlighted. Currently, the challenge is to increase immunization against influenza, a disease with low mortality and hospitalization rates for the population of this study, but with high transmissibility in the general population, with an impact not only on health, but also on social and economic wealth.